Global, regional, and national analyses of the burden of colorectal cancer attributable to diet low in milk from 1990 to 2019: longitudinal observational study - Zhang, Xingxing; Zhang, Xinru; Li, Ruihua; Lin, Meiyan; Ou, Tongyin; Zhou, Hu; Chen, Zhiming; Zhen, Li (Frontiers in Nutrition, 2024)
Background Globally, diet low in milk is the third greatest risk factor for colorectal cancer (CRC). However, there has been a lack of detailed worldwide analysis of the burden and trends of CRC attributable to diet low in milk. Objective We aim to assess the spatiotemporal trends of CRC-related mortality and disability-adjusted life-years (DALYs) attributable to diet low in milk at the global, regional, and national levels from 1990 to 2019. Methods Data of mortality, DALYs, age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) of CRC attributable to diet low in milk were extracted from the Global Burden of Disease (GBD) 2019 study. The burden of CRC attributable to diet low in milk was estimated using the ASMR and ASDR, while accounting for sex, age, country, and socio-demographic index (SDI). From 1990 to 2019, the estimated annual percentage change (EAPC) was calculated to clarify the temporal trends in the ASMR and ASDR attributable to diet low in milk. Results In 2019, there were 166,456 (95% UI = 107,221–226,027) deaths and 3,799,297 (95% UI = 2,457,768–5,124,453) DALYs attributable to diet low in milk, accounting for 15.3 and 15.6% of CRC-related deaths and DALYs in 2019. CRC-related deaths and DALYs attributed to diet low in milk increased by 130.5 and 115.4%, from 1990 to 2019. The burden of CRC attributable to diet low in milk varied notably among regions and nations. High-middle SDI regions had the highest ASDR and ASMR of CRC linked to diet low in milk, while there was a slight downward trend high SDI regions. Among geographical regions, East Asia had the highest number of CRC-related deaths and DALYs attributable to diet low in milk. Notably, the burden of CRC was highest in males and the elderly. With coefficients of −0.36 and −0.36, the EAPC in ASMR and ASDR was significantly inversely correlated with the Human Development Index in 2019. Conclusion Globally, the number of CRC deaths attributable to diet low in milk has continued to increase over the last 30 years. Therefore, government and authorities should conduct education campaigns to encourage individuals to increase daily milk intake.